Identification of candidate gene function group of yeast cell cycle genes using gene expression data - Salido, Julie Ann A. (College of Engineering, University of the Philippines Diliman, 2015)
In various gene expression repositories such as for Saccharomyces Cerevisiae, it is a usual occurence that cell cycle genes are not assigned with biological functions. This is due to current researches focus on gene function discovery using wet laboratory which is time consuming and tedious. This research will focus on the identification of genes' biological functions of yeast, Saccharomyces Cerevisiae involved in cell cycle using time series gene expression data. A method for identifying gene functions that uses Nonmetric Multidimensional Scaling with confidence intervals of 95% and confidence ellipse of 95% is proposed for the computing method for identifying the goodness of fit per group. The results are cross validated as a comparison with the three known databases of Saccharomyces Cerevisiae, Comprehensive Genome Database of Munich Information Center for Protein Sequences, Kyoto Encyclopedia of Genes and Genomes and protein Basic Local Alignment Search Tool of National Center for Biotechnology Information. Using sensitivity analysis of result of identified candidate biological function group compared with the three databases. This method shows a good identification of genes biological functions based on the main characterization of biological phase, using sensitivity analysis associated with confidence interval. The methods were able to give candidate biological function groups to 92.74%, 166 of the 179 unclassified genes.